Dissident Sexualities in Recent Spanish Narrative: Sexual Politics, Cinema y Subversion in Mae West y yo [Mae West and I] (2011) by Eduardo Mendicutti - Saxe, Facundo (Universidad Pedagógica y Tecnológica de Colombia, 2016)
article discusses the narrative work of Spanish writer Eduardo Mendicutti in relation to the representation of sexual dissidence in Spain in the last decades. In particular, this paper focuses on one of the last narrative works of this author, Mae West y yo [Mae West and I] (2011). The article analyzes topics and literary devices directly related to sexual dissidence, from a queer perspective. In this context, the novel operates as an example of the complete works of this author, which would function as a “cultural history” of dissident sexuality in Spain in the last decades